Technika Elastooptycznych Badań Płaskiego Stanu Naprężenia - Pindera, Jerzy Tadeusz (Engineering Transactions, 1955)
This paper gives an outline of the photoelastic method and a general description of the technique of photoelastic investigation of plane states of stress with loads constituted by constant external forces, by means of the surface methods. Some problems are treated in detail. These are: technique of model manufacture, skin and machining effect, measurement methods, the problem of apparatus etc. The author describes an apparatus of his own design and the instruments constituting the basic equipment for a photoelastic laboratory. In view of photoelastic experiments, the skin effect is considered by the author to be linked not only to the stress but also to the secondary orientation birefrigence (resembling the phenomenon of «stress freezing») and to the change of the refraction index resembling the phenomenon known under the name of Schlieren. The author suppresses the influence of optical creep by means of an optical creep compensation device. Discussing the exactness of photoelastic measurement the author considers, among other problems, the influence of faulty loading on the exactness of the photoelastic image.